KRITERIA PENERAPAN AMNESTI OLEH PRESIDEN REPUBLIK INDONESIA - Lase, Martinus; Indra, Mexsasai; Lestari, Maria Maya (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2021)
This research was motivated by giving amnesty to sister Baiq Nuril who triggered various legal problems. Because it’s in a legal habit international and Indonesian constitutional practices, amnesty was only granted to the perpetrator of a politically motivated crime. So that a legal problems, namely the existence of legal uncertainty, absence equality before the law, and contrary to constitutionalism. The research question in this study is about how the criteria for granting amnesty and the ideal concept of granting amnesty? Next for the methodology used in this research is legal research normative, and analyzed qualitatively using Stufenbau theory (stufentheorie) and Hans Kelsen’s theory of positive law. In a draw the conclusion of the author uses the inductive thinking method.Of all the regulations governing the granting of amnesty, the criterion is not clear, even between Article 14 paragraph (2) of the 1945 Constitution and Law no. 11 of 1954 About Amnesty is not harmonious so that it is against stufentheorie. In ideal concept, the President must obtain amnesty approval from the DPR, in order to comply with constitutionalism. However based on analysis that has been done, it can be concluded that the legal basis of giving the criteria for amnesty by the President of the Republic of Indonesia are not clear and tend to be the direction of absolutism. Therefore, ideally the implementation of amnesty by the President Republic of Indonesia, it is based on international legal traditions and traditions Indonesian constitutional law which will be written in the regulations legislation. So the government should give amnesty, first should amend the constitution, make the Presidential Institute Law, amend it The Amnesty Law and changes to the Law on Clemency in order attainment of justice with legal certainty for all Indonesian citizens.Keywords: Amnesty Criteria – Amnesty Concept